2012
DOI: 10.4236/psych.2012.38088
|View full text |Cite
|
Sign up to set email alerts
|

Mapping the Runner’s Mind: A New Methodology for Real-Time Tracking of Cognitions

Abstract: Recording cognitions in real-time while running has been identified as one of the major limitations in the field of sport psychology. In this study, a new methodology was developed to overcome this limitation. For this purpose, 17 competitive long distance runners participated voluntarily. The experimental session consisted in identifying and storing cognitions (thoughts, emotions, sensations and mental images) while performing a 30 minutes treadmill run. In addition, participants were asked to register which … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 16 publications
0
7
0
1
Order By: Relevance
“…En el ámbito de la psicología de la actividad física y de deporte se distinguen dos líneas fundamentales de investigación, la primera que analiza los estados de ánimo desde un enfoque básicamente congnitivo (Quintana, Rivera, De la Vega y Ruiz, 2012;Parry, Chinnasamy, Papadopoulou, Noakes y Micklewright, 2011;Vallerand y Blanchard, 1999) y la segunda formada por las investigaciones cuyo objetivo principal gira en torno a la dimensión motivacional (Deci y Ryan, 1985;Gillet, Berjot, Vallerand, Amoura y Rosnet, 2012;Li et al, 2011;Plessner, 2010). En concreto, la Escala de Motivación Deportiva (EMD) quedaría englobada dentro de la segunda línea de actuación (Vega, Ruiz, Tejero y Rivera, 2014).…”
Section: Introductionunclassified
“…En el ámbito de la psicología de la actividad física y de deporte se distinguen dos líneas fundamentales de investigación, la primera que analiza los estados de ánimo desde un enfoque básicamente congnitivo (Quintana, Rivera, De la Vega y Ruiz, 2012;Parry, Chinnasamy, Papadopoulou, Noakes y Micklewright, 2011;Vallerand y Blanchard, 1999) y la segunda formada por las investigaciones cuyo objetivo principal gira en torno a la dimensión motivacional (Deci y Ryan, 1985;Gillet, Berjot, Vallerand, Amoura y Rosnet, 2012;Li et al, 2011;Plessner, 2010). En concreto, la Escala de Motivación Deportiva (EMD) quedaría englobada dentro de la segunda línea de actuación (Vega, Ruiz, Tejero y Rivera, 2014).…”
Section: Introductionunclassified
“…Cognitions are internal and not directly observable, the stream of cognitions while running is dynamic switching from thoughts to sensations and emotions , Quintana et al, 2012. In the present study was possible to control if participants were using the requested associative and dissociative strategy during every session.…”
Section: Task Effectivenessmentioning
confidence: 92%
“…One of the big difficulties for the assessment of the attentional process is related to their nature, cognitions are internal and not directly observable . The research of Quintana, Rivera, De la Vega, and Ruiz (2012) have shown that stream of cognitions while running is dynamic, switching from thoughts to sensations and emotions. Particularly, long distance running, and the accumulated effort of the activity have shown that cognitions cannot maintain a linear direction (Balagué, Hristovski, Aragonés, and Tenenbaum (2012).…”
Section: Runningmentioning
confidence: 99%
See 2 more Smart Citations